Mark J. Cartledge, A. J. Swoboda, eds., Scripting Pentecost: A Study of Pentecostals, Worship, and Liturgy (Explorations in Practical, Pastoral and Empirical Theology) (Homiletic, 2017)
Please click the PDF button to access the review.